A política de assistência estudantil nas instituições de ensino superior - Lima, Rodrigo Mamédio de (Universidade Federal do Tocantins, 2022)
The present Work of Conclusion of Course aims to give visibility to the results seized on the issue of the Policy of Student Assistance in Higher Education Institutions, with emphasis on the Federal University of Tocantins (UFT) and the Federal Institute of Education, Science and Technology of Tocantins (IFTO). Also highlighting throughout the work the political, economic and social conjuncture in which Brazil is experiencing from 2016 to the present day, post impeachment of the former president Dilma Rousseff. Throughout this research, the importance of the Education Policy and the Student Assistance Policy in the scenario of the Brazilian Higher Education Institutions (IFES), and the importance of the insertion of the social workers in these policies, in the sense of guaranteeing and expanding the access, permanence and completion of graduation with quality, minimizing the social and educational inequalities present in the scope of the IFES. The actions and programs developed in each one of the Teaching Institutions are mentioned here. In order to carry out this work, the following research techniques were used: the bibliographic research, responsible for presenting questions related to the Student Assistance Policy and the documentary analysis, with emphasis on the resolutions on Student Assistance of the Institutions in question. Finally, we emphasize that this debate does not end in the results of this explanatory research, since we defend a Public Education of quality and that provides the necessary subsidies for the young to succeed in the course of their academic formation, also fighting for greater investments in Education as a whole and also in the National Program of Student Assistance (PNAES).